O Programa Nacional de Alimentação Escolar (PNAE) e o desenvolvimento local: estudo de dois modelos de implantação no município de Cerro Largo – RS - Tschiedel, Márcia (2020)
This work brings a research about public policies and development. The lócus of the study is the city of Cerro Largo, sited in the Northwest Region of Rio Grande do Sul. The theoretical references were guided n the thematic about Public Policy and Development, the Educational Public Policies to Nutritive and Nutritional Security Promotion, and lastly, the PNAE in Local Development and Family Farming with Promotion of Short Chains. The investigation is focused in the National School Feeding Program (PNAE), between 2010 and 2018. This period was selected in order to seek for elements about the implementation of the program before the Law 11.947/2009, which establishes that, at least 30% of the resources must be designated to the acquisition of products from the Family farming. To the analysis, two distinct models were selected, one centered in the City Hall, which represents the program in the Municipal Educational System and other decentralized within State School of Basic Education Eugênio Frantz, the side view used to represents the state system. This dissertation is rated as exploratory and qualitative, it uses techniques of collection of bibliographic data, documents and interview in depth with subjects involved in the PNAE context in the city: subject from the City Hall, from the State School and Suppliers from the Program. It brings as a result, a bibliographic review about the program, the city’s historic about the program, aspects about what has changed since Law 11.947/2009, about the established partnerships, about the way how institutions are organized, the structures built for the program, aspects about the management, the purchase steps, deliveries, payment, volume involved and inspection. The construction of a comparative analysis, between the municipal system and the state system, points to their difficulties and the program’s importance to the local development. The difficulties can be listed in three main points: the acquisition of Family farming products, the bureaucracy established about the program and low costs regarding the Federal Government demands. On the other hand, the importance can be highlighted in five points: the resources meaning to the local commerce that creates a nutritional quality, a less impact of transportation and logistics costs; the income to agro industries and local agriculturists; the impact of this nourishment to students and their families and the learning possibility in management terms for commercialization.